On averaging difference equations on an infinite interval - Stanzhitskyi, O.M.; Ateiwi, A.M. (Нелінійні коливання, 2003)
The averaging method on the semi-axis is justified for systems of difference equations. A theorem on
closeness of the corresponding solutions of the exact and averaged systems on the semi-axis is proved. This
theorem is analogous to N. N. Bogoliubov’s second theorem about an averaging method for systems of
difference equations. Наведено метод усереднення на пiвосi для систем рiзницевих рiвнянь. Доведено теорему про
близькiсть розв’язкiв точної та усередненої систем на пiвосi. Дана теорема є аналогом другої
теореми М. М. Боголюбова методу усереднення для систем рiзницевих рiвнянь.